2016
DOI: 10.1615/jlongtermeffmedimplants.2016015197
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Genetic Polymorphisms with Periodontitis and Peri-Implantitis in the Iranian Population: A Literature Review

Abstract: Periodontitis is an infectious disease of the tooth-supporting tissues. Specific periodontal pathogens trigger inflammatory responses and result in progressive bone loss, which eventually leads to exfoliation of teeth. Periimplantitis is the destructive inflammatory process affecting the soft and hard tissues surrounding dental implants. The periodontal pathogens found around failing implants are very similar to those associated with various forms of periodontal diseases. Genetic susceptibility has been known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Different from mucositis, peri-implantitis is an irreversible inflammatory process that affects not only soft tissues but also surrounding supporting bone of implants in occlusal function (7,10,16,17). In fact, dental implant failure is a multifactorial condition, in which genetic polymorphisms can affect levels of gene expression and production or protein functions; as a consequence, they may influence the secretion of inflammatory cytokines and regulate the inflammatory responses and the susceptibility to the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different from mucositis, peri-implantitis is an irreversible inflammatory process that affects not only soft tissues but also surrounding supporting bone of implants in occlusal function (7,10,16,17). In fact, dental implant failure is a multifactorial condition, in which genetic polymorphisms can affect levels of gene expression and production or protein functions; as a consequence, they may influence the secretion of inflammatory cytokines and regulate the inflammatory responses and the susceptibility to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, dental implant failure is a multifactorial condition, in which genetic polymorphisms can affect levels of gene expression and production or protein functions; as a consequence, they may influence the secretion of inflammatory cytokines and regulate the inflammatory responses and the susceptibility to the disease. The RANK/RANKL/OPG system has a significant role in the production and activation of osteoclasts, and therefore in the regulation of bone resorption, possibly affecting the progression of periimplantitis (17,18). Previous studies evaluated the association between genetic polymorphisms with peri-implantitis in different populations (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic susceptibility has been shown to be a significant risk factor for peri-implantitis, and there are numerous studies assessing this in different populations [ 9 , 10 , 11 ]. Gene polymorphisms refer to changes in DNA sequencing, such as the regulation of inflammatory mediators, primarily the gene promoter region, which can affect gene function and the progression of inflammatory diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 5 In addition, recent studies have demonstrated that genetic polymorphism is a major contributor to PI. 6 …”
Section: Introductionmentioning
confidence: 99%